What Do You Think About the Service of Netflix? A Study on The Successful Pathway of Netflix - Yee Goh Xin (Advances in Global Economics and Business Journal, 2023)
Nowadays, cinemas are not the only place to watch a movie. Netflix will become a better choice for everyone to watch movies as well as television drama series. Netflix users are able to watch any movies and television drama series anywhere anytime they wish. Undoubtedly, Netflix is a good platform for everyone to entertain themselves by watching movies as it is very convenient. Hence, this study will examine the factors that affect customer satisfaction with the service provided by the Netflix company in order to make themselves a success in the peer industry. This study employs survey data from Malaysian citizens by spreading the Google Form in media social platforms such as Telegram groups. The result shows Service quality, Brand image, and Brand loyalty are the factors that affect customer satisfaction. Besides that, the findings of this study suggest that Ease of use is the only construct that should be aware of by Netflix company in order to increase customer satisfaction.